Comparison of adverse events following immunisation with acellular and whole-cell pertussis vaccines: A systematic review. Issue 40 (25th September 2018) - Patterson, Jenna; Kagina, Benjamin M.; Gold, Michael; Hussey, Gregory D.; Muloiwa, Rudzani
Abstract: Introduction: Two types of vaccines are currently licensed for use against pertussis: whole-cell (wP) and acellular pertussis (aP). There is evidence that wP confers more durable immunity than aP, however wP has been more frequently associated with adverse events following immunisation (AEFI). A comparison of the frequency of AEFI with the first doses of wP and aP has not yet been clearly documented. This must be done in light of recent considerations to move towards a wP prime-aP boost vaccination strategy in low and middle-income countries. Objectives: To compare the frequency of AEFI associated with the first dose of the wP and aP vaccines. We also compared the frequency of AEFI associated with subsequent doses of wP. Methods: This systematic review was carried out in strict accordance with the published protocol. Results: High heterogeneity amongst included one-armed studies did not allow for pooling of prevalence estimates. The prevalence estimates of AEFI at first vaccine dose of wP ranged from 0 to 75%, while the prevalence estimates of AEFI at first vaccine dose of aP ranges from 0 to 39%. The prevalence estimates of adverse events following second and third vaccine dose of wP ranged from 0 to 71% and 0 to 61%, respectively. Risk ratios among two-armed studies showed an increased risk of adverse events with first dose of wP compared to aP [local reaction RR 2.73 (2.33, 3.21), injection site pain RR 4.15 (3.24, 5.31), injection site swelling RR 4.38 (2.70, 7.12), fever over 38 °C RR 9.21 (5.39, 15.76), drowsiness RR 1.34 (1.18, 1.52) and vomiting RR 1.28 (0.91, 1.79)]. Conclusion: Our results confirm that, when comparing the first dose, wP is more reacotgenic than aP. The proposed wP prime followed by aP boost pertussis vaccine strategy should be approached with caution.